2021
DOI: 10.3390/nano11061512
|View full text |Cite
|
Sign up to set email alerts
|

Shifted Legendre Collocation Method for the Solution of Unsteady Viscous-Ohmic Dissipative Hybrid Ferrofluid Flow over a Cylinder

Abstract: A numerical treatment for the unsteady viscous-Ohmic dissipative flow of hybrid ferrofluid over a contracting cylinder is provided in this study. The hybrid ferrofluid was prepared by mixing a 50% water (H2O) + 50% ethylene glycol (EG) base fluid with a hybrid combination of magnetite (Fe3O4) and cobalt ferrite (CoFe2O4) ferroparticles. Suitable parameters were considered for the conversion of partial differential equations (PDEs) into ordinary differential equations (ODEs). The numerical solutions were establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 26 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Mn-Zn ferrite ferrofluid is underdamped, this occurred because elastic particles are dominated by the system, and the effect is ascribed to a small amount of energy being dissipated by the system [3]. Micron-sized magnetic particles found in magneto rheological fluids undergo quick viscosity changes in response to a magnetic field, providing flexible and reversible damping solutions for use in automotive and engineering systems [4,5]. The magnetic nanofluid is produced as either ferrofluid or magneto rheological fluid (MR fluid), depending on the size of the magnetic fluid particles.…”
Section: Introductionmentioning
confidence: 99%
“…Mn-Zn ferrite ferrofluid is underdamped, this occurred because elastic particles are dominated by the system, and the effect is ascribed to a small amount of energy being dissipated by the system [3]. Micron-sized magnetic particles found in magneto rheological fluids undergo quick viscosity changes in response to a magnetic field, providing flexible and reversible damping solutions for use in automotive and engineering systems [4,5]. The magnetic nanofluid is produced as either ferrofluid or magneto rheological fluid (MR fluid), depending on the size of the magnetic fluid particles.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, hybrid ferrofluids are the combination of two solid ferromagnetic particles with a conventional heat exchange fluid like water, ethylene glycol or their mixture (water-ethylene glycol). Several studies numerically demonstrated the development of heat transfer rate in ferrofluids (see Anuar et al, [2], Saranya et al, [3], Waini et al, [4] and Hamid et al, [5]). The heat generation physically affects the distribution of temperature in the engineering applications like semiconductor wafers, electronic chips and nuclear reactors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 34 conducted an analysis of the effect of Joule heating on the flow of nanofluid through a permeable conduit. While this was going on, Saranya et al 35 noticed how the hybrid ferrofluid flow through a contracting cylinder was affected by viscous dissipation and Joule heating. They employ a base fluid mixture of water (50%) and ethylene glycol (50%) along with magnetite-cobalt ferrite hybrid nanoparticles in their study.…”
Section: Introductionmentioning
confidence: 99%